The Effectiveness of Interview Technique in Improving Students’ Speaking Ability - Sonya V. Ch. Benu; Dian R. Sabat; Rosalina S. S. Son; Berthi O. Tunu (Pusat Kegiatan Belajar Masyarakat (PKBM) Sambi Poleng, 2023)
This study aimed to confirm how effective interview technique in improving students speaking skill. There were 30 junior high school students as the participants. The participants taken from random schools. They were in one community in Kuatae Village. The researchers used experimental method and collected the data by using test, in the form of pre-test and post-test to check how far the progress of students’ speaking by using interview technique. The result of this study indicated that using interview technique could improve students’ speaking ability. Their improvement covered that the students had a lot of chances to interact with their partners and the teachers. They were also becoming more confident in speaking by using English. Interview technique could be a choice for the next researchers to dig more information about the strengths of interview for the improvement of English in speaking or other skills.